Aspect Regarding the Design of Active Strategies for Venture Capital Financing – the Flexible Adjustment for Romania as a Frontier Capital Market - Gabriela Prelipcean; Mircea Boscoianu (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Rovinj, Croatia, 12-14 September 2019, 2019)
Industry 4.0 revolution find a real interest of entrepreneurs but in the case of frontier and emerging markets it is difficult to find a reliable source of long-term financing. The decoupling of the technological evolution from the evolution of the access to financing capacities must be analysed from different point of view (financial, legislative, socio- technical). In Romania, as a frontier market there are only few alternative investment solutions capable to respond to the long-term financing demand of performant projects. The main interest is to understand the strategies for adaptation of venture capital fund (VCF) at real conditions. Venture capital funds (VCF) represents a particular form of private equity investments, scale down and more focused on innovative start-up (or even expansions on technology or markets) projects (the typical value is 10 mil Euro). This form of investments is a personalized response to the general problem related to the actors that do not have tangible assets for collaterals and / or cannot demonstrate the ability to make a profit. In the case of VCF, as a vehicle oriented on innovation and technology, the business plan represents the main element for project portfolio selection in the context of matching the interests of investors with the interests of financed firm's managers. This contribution is especially important for the case of frontier and emerging markets characterized by additional restrictions (access to strategies, liquidity problems, and agency costs beyond a simple monitoring). For Romania, it is essential to adapt VCF investors' objectives to all phases (selection, evaluation, contract signing and restructuring, progress monitoring, stimulating value-added and, especially, closing the VCF cycle) to real conditions and considering the performance indicators balancing with the value creation mechanisms specific of industry 4.0.
Keywords: G24; M13; O16; 330; venture capital fund VCF; innovative start-up projects; business plan; active selection